Adverse Drug Reactions and Clinical Outcomes in Patients Initiated on Antiretroviral Therapy: A Prospective Cohort Study From Ethiopia - Bezabhe, W.; Bereznicki, L.; Stafford, Leanne; Gee, P.; Kassie, D.; Bimirew, M.; Peterson, G. (2015)
© 2015, Springer International Publishing Switzerland.Introduction: In Ethiopia, the use of antiretroviral therapy (ART) has been scaled up for HIV/AIDS over the past decade. Adverse drug reactions (ADRs) associated with ART pose a unique challenge in the treatment of the infection in this resource-limited setting. Objectives: The aims of this study were to examine the incidence and nature of ADRs, identify the risk factors associated with the development of ADRs, and assess their impact on treatment outcomes. Methods: A prospective cohort study was conducted in adult patients (=18 years of age) with HIV/AIDS who commenced ART. All ADRs in the first 12 months of therapy were recorded, and the severity, causality, and preventability assessed. The impact of severe ADRs on self-reported adherence, immunological, and body mass index (BMI) outcomes were assessed. Results: Of the 211 patients included in the analysis, 181 (85.7 %) experienced at least one ADR and 66 (31.3 %) experienced at least one severe ADR within 12 months of commencing ART (incidence rates for any ADR and severe ADR of 14.8 and 3.2 per 100 person-months, respectively). Logistic regression analysis indicated that taking zidovudine-containing regimens (odds ratio [OR] 4.2, 95 % confidence interval [CI] 2.1–8.4) or being unemployed (OR 2.2, 95 % CI 1.1–4.3) were independent predictors of experiencing severe ADRs. Patients who experienced a severe ADR were less likely (OR 0.4, 95 % CI 0.2–0.9) to be =90 % adherent to ART. The mean gain in BMI was significantly lower in patients with severe ADRs after 3 and 12 months of therapy. Conclusions: ADRs were common within the first 3 months in patients initiated on ART. Severe ADRs were negatively associated with self-reported adherence and gain in BMI. Measures need to be implemented to routinely monitor for severe ADRs to improve ART adherence and treatment outcomes.